2019
DOI: 10.1155/2019/6149189
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Synthesized Zeolite for Improved Properties of Pyrolytic Oil Derived from Used Tire

Abstract: This paper reports the investigation of zeolite NaY synthesized from kaolin, a locally abundant soil material found in the Benin City metropolis, Nigeria, as a suitable catalyst and its effect on the properties of pyrolytic oil produced from used tires. The pyrolysis process was conducted from a range of 1 to 10 wt.% of catalyst concentration to the used tire at an operating temperature of 600°C, heating rate of 15°C/min, and particle size of 6 mm. An increase in the catalyst weight gave a maximum yield of cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…could be attained from the pyrolysis of waste tires at pyrolysis temperature of 600 °C and a heating rate of 15 °C./minute using zeolite catalyst ratio to waste tires of 7.5 %-wt. [10]. The different trends for TPO yields with heating rates and pyrolysis temperature have been reported by some researchers.…”
Section: Products From Waste Tire Pyrolysismentioning
confidence: 81%
See 2 more Smart Citations
“…could be attained from the pyrolysis of waste tires at pyrolysis temperature of 600 °C and a heating rate of 15 °C./minute using zeolite catalyst ratio to waste tires of 7.5 %-wt. [10]. The different trends for TPO yields with heating rates and pyrolysis temperature have been reported by some researchers.…”
Section: Products From Waste Tire Pyrolysismentioning
confidence: 81%
“…and a pyrolysis temperature of 600 °C with a heating rate of 15 °C./minute. The yield of PLO was lower than the yield of non-catalyzed TPO of 34.40 %-wt., nevertheless, the quality in terms of the range of hydrocarbon fuels produced gasoline (C6-C12) is higher than that of non-catalyzed PLO [10]. The PLO yields from 31.6 to 12.7 %-wt.…”
Section: Zeolite Catalytic Pyrolysis Of Waste Tirementioning
confidence: 95%
See 1 more Smart Citation
“…The TDO produced when using catalysts showed improvements in physical properties and resembled those of commercial diesel. Osayi and Osifo 34 conducted a study comparing the physical properties of uncatalysed and catalysed (zeolite NaY catalyst) TDO and commercial diesel. The reported results showed that some of the properties were not affected such as density, viscosity, flash point and pour point and some properties were improved in the catalysed oil such as refractive index, heating value and sulfur content.…”
Section: Introductionmentioning
confidence: 99%
“…Kaolin also has a high molecular stability, with isomorphous substitutions being rare or non-existent and environmentally friendly. Several researchers have modified the chemical and physicochemical properties of zeolite with kaolin to create catalyst [15][16][17]. Nevertheless, as zeolites have different properties affecting their capability, further research is required to evaluate the potential of other types of zeolites such as clinoptilolite.…”
Section: Introductionmentioning
confidence: 99%